Acquired Ano Rectal Conditions (AARC) in Children Seen at Gezira National Center for Pediatric Surgery (GNCPS-Sudan), Epidemiology, Management, and Outcome - KY Abuaagla; Ahmed A Abdalla; Faisal A Nugud (Tropical Health and Medical Research, 2021)
The study's main objective is to determine the epidemiology, treatment, and outcome of the acquired anorectal conditions seen at the GNCPS. This study was a retrospective and prospective descriptive hospital-based study involving (131) child with Acquired anorectal conditions (AARC) who presented to GNCPS during the two-year study period. Data regarding the presentation, management, and post-operative course to look after complications and outcomes were collected. Data were collected using a formulated questionnaire and analyzed using (SPSS 17). Data considered statistically significant when P-value is less than 0.05. The study involved a total number of 131 children with AACS. The mean age of presentation is (5.78 years) with an overall 1.4:1 male to female ratio. Most of the study subjects are from rural areas, 66.4 percent. Most of them treated surgically, 83.2 percent, and 16.8 percent medically, with an overall complication rate of 24.4 percent. Conclusion Acquired Ano Rectal Conditions commonly seen at the preschooler age, mean (5.78 years). Rectal polyps and rectal prolapse were among the most frequently seen acquired anorectal conditions in children. Most of the cases treated surgically with an overall complication rate of 24.4 percent.